How to Manage The Liquidity and Fight The Firm Debt - Yanko Hristozov (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2018)
The liquidity is one of the most popular and used financial indicators for solvency at enterprises. The present study attempts to identify the key factors of managing the liquidity in enterprises, and the ability of influence by financial managers on them in order to provide